Analisis Bibliometrik: Artificial Intelligence dan Otak dalam Neuropsikologi - Pramesti, Amelia Cahaya; Aristawati, Nina Vania; Wikantyasning, Dhefira Elshafa Dyah; Salsabilla, Autasya Safira; Kusrohmaniah, Sri; Sulastri, Augustina (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This research aims to visualize research trends regarding the relationship between Artificial Intelligence (AI) and the human brain through bibliometric analysis. Data was obtained from the Scopus database of 1424 documents from 1983-2024. The results of this research found that artificial intelligence and the brain have developed increasingly rapidly in recent years along with technological developments. A better understanding of the distribution and trends of this research will hopefully reveal key concepts that support the development of AI and its impact on the human brain.